Analisa Pengujian Lelah Material Bronze Dengan Menggunakan Rotary Bending Fatigue Machine - Rahmatullah Rahmatullah; Rohadi Ahmad (Rekayasa Material, Manufaktur dan Energi, 2018)
Is a material fatigue due to repeated loading. damage caused by repeated loads (Fatigue Failures), The test is carried out as much as 5 x using a fatigue tester, With the Rotary Bending type the load variations are given as follows: 10kg, 15kg, 20kg, 25kg, and 30kg. fatigue is very dangerous compared to static failure because the failure occurred without warning, or suddenly and in a rush, Experiment 1: Cycle with 22741 with a time of 12.06 minutes given a load of 10 Kg with the results of calculation = 34.226 Mpa, Experiment 2: Cycle with 20786 with a time of 11.59 minutes given a load of 15 Kg with the results of calculations = 51,339 Mpa, Experiment 3: Cycle with 17033 with time 11,39 minutes given load 20 Kg with result of calculation = 68,45 Mpa, Experiment 4: Cycle with 8640 with time 06,39 Minutes given load 25 Kg with result of calculation = 83,333 Mpa, Experiment 5: The cycle with 4541 with a time of 03.27 minutes was given a load of 30 Kg with the result of calculation = 102.667 Mpa. With conclusions as follows, Bronze Tired Resistance decreases as the voltage increases.